Postoperative adjuvant therapy for patients with loco-regionally advanced oral squamous cell carcinoma who are at high risk of recurrence. Issue 7 (July 2020) - Yanamoto, S.; Denda, Y.; Ota, Y.; Hasegawa, T.; Akashi, M.; Okura, M.; Yamada, S.-I.; Kurita, H.; Yamakawa, N.; Kirita, T.; Ueda, M.; Umeda, M.; et al.
Abstract: Extranodal extension (ENE) of lymph node metastasis and the presence of a positive or close margin (PCM) are major risk factors for head and neck squamous cell carcinoma recurrence. This retrospective multicentre cohort study compared the prognostic impact of postoperative radiotherapy (RT) and concurrent chemoradiotherapy (CCRT) in oral squamous cell carcinoma (OSCC) patients at high risk of recurrence. One hundred and eighteen patients with PCM and/or ENE who underwent definitive surgery plus either adjuvant RT or CCRT using cisplatin for OSCC were investigated. The cohort-wide 5-year loco-regional control (LRC), disease-free survival (DFS), and overall survival (OS) rates (the main outcome measures) were 54.3%, 35.8%, and 43.2%, respectively. Multivariate analysis showed that age ≥64 years (hazard ratio (HR) 0.584), cT3–4 stage (HR 1.927), ≥4 metastatic lymph nodes (HR 1.912), and PCM (HR 2.014) were significant independent predictors of OS. Moreover, postoperative CCRT with cisplatin was associated with a significantly improved LRC rate, but not with improved DFS or OS rates, compared to postoperative RT (HR 0.360). Given that CCRT with cisplatin does not significantly improve survival, additional clinical trials will be required to validate new regimens that further improve the outcomes of patients with loco-regionally advanced OSCC going forward.